Samuel Franklin Emmons papers - Emmons, Samuel Franklin, 1841-1911.; Bartlett, Suzanne Earle Ogden-Jones Emmons, 1861-1954.; Markoe, Sophie D.
Correspondence, letterbooks, diaries and field notes, family papers, subject files, financial records, scrapbooks, printed matter, photographs, and other papers relating chiefly to Emmons's career as a geologist and to his family. Documents his explorations in the western United States including the United States Geological Exploration of the Fortieth Parallel, 1867-1876; geological formations and mines and mining; and the U.S. Geological Survey, cofounded by Emmons and Clarence King. Family papers includes correspondence with Emmon's uncle, N. Henry Evans, and papers of Emmon's wives, Sophie D. Markoe and Suzanne Earle Ogden-Jones Emmons Bartlett.
Microfilm edition of a diary (1872) available
Microfilm produced from originals in the Manuscript Division.
Collection material in English, with French, German, Italian, and Spanish.
Geologist.
Finding aid available in the Library of Congress Manuscript Reading Room and at
In 1981, papers relating to Paul W. Bartlett and Bessie McPherson were transferred from this collection to the Paul W. Bartlett papers in the Manuscript Division.
Keywords: Evans, N. Henry -- Correspondence; King, Clarence, -- 1842-1901.; Emmons family; Geological Survey (U.S.); Geology; Formations (Geology); Mineral industries; Mines and mineral resources; West (U.S.) -- Discovery and exploration; Geologists